The Effect of Pricing and Operational Cost Control on the Profitability of LTA Wedding in Pagar Alam City - Tiara Julianti; Elvera Elvera; Zulaiha Zulaiha (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the effect of pricing strategy and operational cost control on the profitability of LTA Wedding in Pagar Alam City. This research employed a quantitative method with an associative approach. The sample consisted of 35 monthly financial reports for the period 2023–2025, which were analyzed using multiple linear regression analysis. The results indicate that pricing strategy and operational cost control have a positive and significant effect on profitability. This is evidenced by the t-test with a significance value of 0.000 < 0.05 and the F-test with an F-value of 13.325 and a significance value of 0.000 < 0.05. The coefficient of determination (Adjusted R Square) of 0.862 indicates that 86.2% of profitability is explained by pricing strategy and operational cost control, while the remaining 13.8% is influenced by other factors outside the scope of this study. Therefore, the more appropriate the pricing strategy and the more effective the operational cost control, the higher the profitability achieved by LTA Wedding in Pagar Alam City.